1989
DOI: 10.1111/j.1365-3113.1989.tb00280.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cretaceous dance fly (Diptera: Empididae) from Botswana

Abstract: The first fossil dance fly, Empis (s.s.) orapaensis sp.nov., of the subfamily Empidinae (Diptera: Empididae) is described from Africa. It was extracted from middle Cretaceous sediments of Orapa, Botswana. Empis orapaensis manifests a more plesiomorphous wing venational pattern then the extant species of Empis, and a list of the apomorphic and plesiomorphic characteristics is given. The specimen modifies earlier ideas on the phylogeny of the Empidoidea.The fossil also provides us with more conclusive evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The presence of deciduous leaves, together with a southerly shift in the presentday distributions of several taxa: Empidae (Waters 1989), Bibionidae (Rayner 1987), Promecognathinae (McKay 1990), suggest that the palaeoclimate of Orapa was both seasonal, and cooler and wetter than found today. Plant remains are predominately from angiosperms and the diversity of leaf types (entire and serrated margins) suggest a mixed successional vegetation within the crater being periodically disturbed by mass flows from the unstable slopes.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of deciduous leaves, together with a southerly shift in the presentday distributions of several taxa: Empidae (Waters 1989), Bibionidae (Rayner 1987), Promecognathinae (McKay 1990), suggest that the palaeoclimate of Orapa was both seasonal, and cooler and wetter than found today. Plant remains are predominately from angiosperms and the diversity of leaf types (entire and serrated margins) suggest a mixed successional vegetation within the crater being periodically disturbed by mass flows from the unstable slopes.…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of Mesozoic compression fossils has been assigned to Empidoidea, some of which date back to the Middle Jurassic, while others have been assigned to present‐day genera (e.g. Waters, 1989). Reconstructing phylogenetic affinities of these fossils often is problematic, as the only reliable features are wing veins, which are rather conservative across the clade and therefore largely uninformative.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their ecology, where they are dependent on flowing water, adults would rarely be associated with tree trunks and other sources of amber, as hypothesized by Sinclair (). Based on fossil Empidinae and Hybotinae, Waters () suggested that these two lineages may actually have been well established by the early Late Cretaceous 93 Ma, or even the Lower Cretaceous, as suggested by Grimaldi & Cumming (), which is much earlier than suggested by Chvála (). Based on this evidence and on present distribution patterns, it is likely that the Clinocerinae were also well established as early as the Cenomanian period (97–91 Ma) of the Late Cretaceous (Sinclair, ).…”
Section: Introductionmentioning
confidence: 95%